Peningkatkan Keterampilan Sosial melalui Penerapan TGT-GI Berbasis Lesson Study - MUMPUNI, KISTANTIA ELOK; SUSILO, HERAWATI; MAHANAL, SUSRIYATI; PRIHATNAWATI, YAYUK (Bioedukasi: Jurnal Pendidikan Biologi, 2014)
Trend of Learning of XXI century  is full of skills, one of skills is social skill. In fact, learning by rote is the most applicated in junior high school in Indonesia. One example of junior high school happened in VIIIB class of UM laboratory  school. Module system has been applying there. It causes individual learning so that reduces the social interaction and social skill. One of the solutions for this problem is TGT-GI strategy, it is included to cooperation model of learning.  This research is conducted based on lesson study class action. Aim of the research is to improve student’s social skill by application of TGT-GI strategy in VIIIB Class of UM Laboratory Junior High School. The results of this research shows the average of student’s social skills was 19,34 % increased. In wich 32,44 in the I cycle and 38,71 in the II cycle. Based on this result, it was clocluded that TGT-GI strategy able to improve student’s social skills in VIIIB Class of UM Laboratory Junior High School.